2019
DOI: 10.3389/fped.2019.00271
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Biomarkers in Amniotic Fluid, Umbilical Arterial Blood, Umbilical Venous Blood, and Maternal Blood at Delivery, and Their Reference Values for Full-Term, Singleton, Cesarean Deliveries

Abstract: Background: Several cardiovascular biomarkers have regulatory functions in perinatal physiology. Aim: This study aimed to analyze the feto-maternal distribution pattern of biomarkers in samples of amniotic fluid, umbilical arterial blood, umbilical venous blood, and maternal blood samples, and to establish reference values. Each linked sample set consisted of the combined samples obtained in an individual pregnancy. Study design: We performed a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…While previous, smaller studies have reported stable levels of NT-pro BNP throughout pregnancy [ 17 , 27 ], our study is consistent with the findings of Blohm et al, who reported lower levels at term [ 28 ]. BNP was comparatively consistent across different gestational ages and it did not require trimester-specific adjustment, nor was it associated with BMI or birthweight.…”
Section: Discussionsupporting
confidence: 92%
“…While previous, smaller studies have reported stable levels of NT-pro BNP throughout pregnancy [ 17 , 27 ], our study is consistent with the findings of Blohm et al, who reported lower levels at term [ 28 ]. BNP was comparatively consistent across different gestational ages and it did not require trimester-specific adjustment, nor was it associated with BMI or birthweight.…”
Section: Discussionsupporting
confidence: 92%
“…The studies included in the systematic review are presented in Table 1 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of filtration (transport) of cardiospecific Tn molecules from the bloodstream to other biological fluids are not investigated, and, accordingly, these possibilities of non-invasive diagnostics have not been validated. Thus, the study of the metabolic pathway of cardiospecific Tns and potential factors influencing it is a relatively large and poorly studied area for further research that is needed to optimize diagnostics and validate new diagnostic capabilities( Stefanovic and Loukovaara, 2005 ; Zhu et al, 2007 ; Van Mieghem et al, 2010 ; Yoshida et al, 2013 ; Blohm et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%